Co‐morbid personality disorder in early intervention psychosis clients is associated with greater key worker emotional involvement. Issue 2 (10th November 2015) - Fornells‐Ambrojo, Miriam; Pocock, Phil; Mintah, Ruth; Barker, Chris; Craig, Thomas; Lappin, Julia M.
Abstract: Aim: Co‐morbid personality disorder (PD) is associated with poorer outcomes in psychosis patients, but it is not known whether these patterns are present at illness onset. This study investigated the prevalence of co‐morbid PD in clients of an Early Intervention in Psychosis Service (EIPS) and compared key worker engagement and service use between patients with and without co‐morbid PD. Method: Forty‐nine participants were recruited from an inner London NHS EIPS. The Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders IV (DSM‐IV) Axis II Disorders was administered to identify whether participants met criteria for a diagnosis of PD. Key workers completed measures investigating the therapeutic relationship and emotional involvement. Data on service use over a 2‐year period from the date on which the patient was accepted by the EIPS were collected from electronic clinical records. Service use and key worker informed data were collected blind to PD diagnosis. Results: Twenty‐two of the 49 (45%) patients met criteria for co‐morbid PD. Keyworker worry and tension were significantly higher in relation to patients with co‐morbid PD compared with those without. There were no significant differences between groups in appointments offered or attended, but patients with co‐morbid PD were significantly less likely to be admitted to hospital than those without. Conclusions: Co‐morbid PD is common in EIPS patients. The EIPS model is both assertive and intensive; although this appears to be effective in preventing hospital admissions, this does not equip professionals to manage the higher emotional burden associated with a co‐morbid PD diagnosis.